2020
DOI: 10.3390/cancers12123774
|View full text |Cite
|
Sign up to set email alerts
|

GAS2L1 Is a Potential Biomarker of Circulating Tumor Cells in Pancreatic Cancer

Abstract: Pancreatic cancer is a malignant disease with high mortality and a dismal prognosis. Circulating tumor cell (CTC) detection and characterization have emerged as essential techniques for early detection, prognostication, and liquid biopsy in many solid malignancies. Unfortunately, due to the low EPCAM expression in pancreatic cancer CTCs, no specific marker is available to identify and isolate this rare cell population. This study analyzed single-cell RNA sequencing profiles of pancreatic CTCs from a geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…CLIC4 knockdown suppressed cell growth and apoptosis, and apoptosis induction by FxOH was reduced with CLIC4 knockdown. The expression levels of CLIC4 and GAS2L1 were found to be higher in circulating tumor cells (CTCs) from pancreatic cancer patients compared to peripheral blood mononuclear cells [93]. Besides, the overexpression of CLIC4 was associated with unfavorable outcomes in multiple cohorts of CN-AML patients [33].…”
Section: Pathway 3: Ctla4-cd2mentioning
confidence: 99%
“…CLIC4 knockdown suppressed cell growth and apoptosis, and apoptosis induction by FxOH was reduced with CLIC4 knockdown. The expression levels of CLIC4 and GAS2L1 were found to be higher in circulating tumor cells (CTCs) from pancreatic cancer patients compared to peripheral blood mononuclear cells [93]. Besides, the overexpression of CLIC4 was associated with unfavorable outcomes in multiple cohorts of CN-AML patients [33].…”
Section: Pathway 3: Ctla4-cd2mentioning
confidence: 99%
“…Specific biomarker identification using single-cell approaches has mainly been performed in the context of oncology. [139][140][141][142] In the context of SOT, Lei et al 143 recently identified Cat-S and PAR-2 as potential therapeutic targets in acute renal allograft rejection. Via similar approaches, novel diagnostic biomarkers that predict the risk of allograft rejection or tolerance can be discovered.…”
Section: Biomarker Identification and Risk Stratificationmentioning
confidence: 99%
“…The main therapies currently include surgery, chemo-/radiotherapy, immunotherapy and targeted drugs, such as inhibitors for vascular endothelial growth factor or EGFR [8][9][10][11][12]. Early detection is important for cancer diagnosis; however, as effective screening methods for PC are limited, most patients are diagnosed in the mid-late stage of the disease [13][14][15]. In addition, high metastatic potential and resistance to chemotherapy result in poor patient outcomes [16,17].…”
Section: Introductionmentioning
confidence: 99%